Peran Orang Tua dalam Meningkatkan Kemandirian Belajar pada Anak di PAUD SKB Sidoarjo - Rahmawati, Lina Aulia; Susilo, Heryanto (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The objectives of this study are: 1) to find out the role of parents in shaping independent learning in PAUD SKB Sidoarjo; 2) to find out the independence of children's learning in PAUD SKB Sidoarjo; 3) to find out the supporting factors for parents in increasing children's independent learning in PAUD SKB Sidoarjo; 4) to find out the parent's obstacles in increasing children's independent learning in PAUD SKB Sidoarjo. This research used a qualitative descriptive method. The nature of descriptive qualitative research is to describe the phenomena in an in-depth description of the field. Data collection techniques used are observation, interview, and documentation techniques. While the data analysis is done through data collection, data reduction, data display, and conclusion. The results showed that: 1) The parent's role in shaping children's independent learning in PAUD SKB Sidoarjo is good enough. There are three roles performed by parents, namely the role as a facilitator, the role as a motivator, and the role as a guide. 2) Children's Independent learning in PAUD SKB Sidoarjo has been well fulfilled, but still not optimal yet. 3) The factors that support parents in improving children's independent learning at PAUD SKB Sidoarjo are giving praise, gifts, and attention. 4) Parent's Obstacles in improving children's independent learning at PAUD SKB Sidoarjo is the difficulty of the children to learn for various reasons.